Exploring grape juice volatile compounds after inactive yeast extract foliar treatment using SPME and GC–MS - Moro, Laís [UNESP]; dos Santos, David Fernando; Furlan, Mara Fernandes Moura; Tavares, Armando Reis; Hernandes, José Luiz; Purgatto, Eduardo; Tecchio, Marco Antonio [UNESP] (Springer Nature, 2025)
This research aims to investigate the effects of foliar application of selected inactivated yeast on grape varieties of juice ('Isabel', 'Isabel Precoce', 'Ives', 'Concord', and 'BRS Violeta') cultivated at the Centro Avançado de Pesquisa e Desenvolvimento de Frutas of the Instituto Agronômico (IAC), using vertical shoot-positioning and trellis systems. The experimental design utilized was a randomized block layout with four replicates. The study evaluated plant productivity and physical characteristics of clusters and berries. Furthermore, the grape juice extracted from these grape varieties underwent analysis for volatile compounds in a two-year study period. The volatile profile of the grape juice was determined using headspace solid phase microextraction (SPME) coupled with gas chromatography combined with mass spectrometry (GC–MS). At the end of this research, despite the application of yeast extract, no significant impact on vine productivity or the physicochemical parameters of the berries was observed. The varieties exhibited distinct responses to the treatment, with 'Isabel' showing the least responsiveness while 'Ives' demonstrated the most significant response. Overall, the treatment was most effective in influencing esters, followed by ketones. This indicates that the impact of the treatment varied across different grape varieties and volatile compositions, highlighting the importance of considering varietal differences in grape cultivation practices and product quality.
Keywords: Elicitors; Preharvest; Saccharomyces cerevisiae; Training systems; Vitis labrusca